2013
DOI: 10.1159/000350788
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Use of a Skin Prick Test Device on Children

Abstract: Background: Studies comparing skin prick test (SPT) devices have revealed varying results in performance and there is little known about their use on children. Methods: We performed 2 complementary studies to test the sensitivity, reproducibility and acceptability of commercially available SPT devices (Stallerpoint, Antony, France) using different application techniques. In the first part, histamine/saline was put on as a drop by use of a vial (V), and in the second part it was transferred from a well with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 10 publications
2
27
1
1
Order By: Relevance
“…The accuracy of these tests depends on a broad range of factors, including allergen potency, allergen content and stability of the allergen test solution, individual skills of the tester (e.g. depth of puncture), status of skin reactivity, application devices , patients’ medication and others . In our previous study , a biochemical analysis of mould SPT solutions revealed both quantitative and qualitative differences depending not only on the mould species, but more specifically on the manufacturer.…”
Section: Introductionmentioning
confidence: 92%
“…The accuracy of these tests depends on a broad range of factors, including allergen potency, allergen content and stability of the allergen test solution, individual skills of the tester (e.g. depth of puncture), status of skin reactivity, application devices , patients’ medication and others . In our previous study , a biochemical analysis of mould SPT solutions revealed both quantitative and qualitative differences depending not only on the mould species, but more specifically on the manufacturer.…”
Section: Introductionmentioning
confidence: 92%
“…found that the Stallerpoint ® device is less sensitive than the ALK lancet or IV needle, but that the 90° clockwise rotation improves the sensitivity of this technique. However, this technique was described by Buyuktiryaki et al . to be reliable, tolerable, and comparable with the ALK lancet technique.…”
Section: Discussionmentioning
confidence: 99%
“…The AUCs obtained with SPT were not different from those obtained with sIgE, except for a significantly lower AUC with SPT for AH by seasonal aeroallergens and for food allergy by peanut ( found that the Stallerpoint â device is less sensitive than the ALK lancet or IV needle, but that the 90°clockwise rotation improves the sensitivity of this technique. However, this technique was described by Buyuktiryaki et al 16 to be reliable, tolerable, and comparable with the ALK lancet technique. As reported in the EAACI position paper on skin prick testing, 17 the protein and antigen content can differ from one commercial SPT solution to another.…”
Section: Agreement Between Spts and Specific Igementioning
confidence: 99%
“…Bu aletlerin duyarlılık ve özgüllüğünü karşılaştıran araştırmalar farklı sonuçlar ve yetersizlikler rapor etmektedir (12)(13)(14). Önemli olan; kullanılacak aletin her bir klinik tarafından pozitif ve negatif kontroller kullanılarak test edilmesi ve uygun kullanma metodunun ortaya konmuş olmasıdır (15). Benzer şekilde testleri uygulayacak sağlık çalışanı eğer bir allerji ve klinik immünolojisi uzmanı olamayacaksa o sağlık çalışanının uygun eğitim teknikleri açısından yetiştirilmiş olması ve yeterliliğinin düzenli aralıklarla (örneğin yılda bir) değerlendirilmesi gerekir.…”
Section: Allerji Deri Test Aletlerinin Kullanımı Nasıl Standardize Edunclassified